Perinatal lethal form Gaucher disease with compound heterozygosity of single nucleotide variants and copy number variations presenting as nonimmune hydrops fetalis and cerebellar hypoplasia: A case report - Chin-Chieh Hsu; Ni-Chung Lee; Yin-Hsiu Chien; Chao-Fan Liu; Yao-Lung Chang (Elsevier, 2024)
Objective: To present the ultrasound imaging and genetic diagnosis of a fetus with prenatal lethal form of Gaucher disease. Case report: A 37-year-old primiparous woman was pregnant at her 23 weeks of gestation and the prenatal fetal ultrasound revealed hydrops fetalis, cerebellum hypoplasia, and fetal immobility. The pregnancy was terminated due to major fetal anomaly, and whole exome sequencing (WES) analysis of fetal tissue and parental blood unveiled a pathogenic variant in exon 10 of the GBA gene (NM_001005741.3: c.1265T > G: p.L422R) originating from the mother. Additionally, a novel CNV (chr1: 155204785-155205635 deletion, 0.85 kb) spanning exon 10-12 in the GBA gene was identified from the father. This compound heterozygosity confirmed the diagnosis of prenatal lethal form of Gaucher disease and was informative for genetic counseling. Conclusion: WES is a powerful tool to detect pathogenic variants among fetuses with nonimmune hydrops fetalis and complex abnormality from prenatal ultrasound. Compound heterozygosity consisted of single nucleotide variants (SNV) and copy number variations (CNVs) may lead rare inherited metabolic disorders including prenatal lethal form of Gaucher disease.